IMPACT OF TRANSFORMATIONAL LEADERSHIP BEHAVIORS ORGANIZATIONAL EFFECTIVENESS IN THE MANUFACTURING INDUSTRY OF SHENZHEN, CHINA: MEDIATING ROLE OF KNOWLEDGE SHARING - Xiong Xu; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
In the dynamic and competitive industrial landscape of Shenzhen, China, where technological advancements and rapid developments are the norm, effective leadership becomes instrumental in driving organizational success. This paper investigates the influence of transformational leadership behaviors on organizational performance within the manufacturing sector of Shenzhen. Drawing upon the framework, which delineates four core components of transformational leadership—Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individual Consideration—this study aims to unravel their implications in the context of Shenzhen's manufacturing industry. Through a comprehensive analysis of these leadership attributes, we seek to provide insights into how leaders can effectively navigate the challenges and opportunities inherent in this dynamic environment. Additionally, this research explores the role of knowledge sharing as a potential mediator in the relationship between transformational leadership and organizational performance. By examining the intricate interplay between leadership behaviors and organizational outcomes, this study contributes to the existing literature on leadership in industrial settings and offers practical